Serum Level of Antibody against Benzo[a]pyrene-7,8-diol-9,10-epoxide-DNA Adducts in People Dermally Exposed to PAHs - Lenka Borska; Ctirad Andrys; Jan Krejsek; Vladimir Palicka; Marcela Chmelarova; Kvetoslava Hamakova; Jan Kremlacek; Pavel Borsky; Zdenek Fiala (Journal of Immunology Research)
Some specific antibodies indicate the presence of antigenic structures on DNA (DNA adducts) that can play an important role in the process of mutagenesis and/or carcinogenesis. They indicate the presence of increased genotoxic potential (hazard) prior to the formation of disease (primary prevention). The present study was focused on the serum level of benzo[a]pyrene 7,8-diol-9,10-epoxide-DNA adducts antibodies (anti-BPDE-DNA) in psoriatic patients (n=55) dermally exposed to different levels of polycyclic aromatic hydrocarbons (PAHs). The general goal of the study was to contribute to better understanding of the value of the assumed biomarker (anti-BPDE-DNA) for evaluation of the organism's answer to genotoxic exposure to PAHs. Elevated level of exposure to PAHs resulted in the increased level of anti-BPDE-DNA. However, almost all levels of anti-BPDE-DNA ranged within the field of low values. Both variants of GT (CCT-3% and CCT-5%) induced higher expression of anti-BPDE-DNA in the group of nonsmokers. Significant relations between the level of anti-BPDE-DNA and PASI score, total duration of the therapy, or time of UVR exposure were not found. Further studies are needed to reduce interpretation uncertainty of this promising bioindicator.